Interactive Learning Technologies to Build Students' Interest in Cross-Cultural Communication - YE I Polyakova (Peoples' Friendship University of Russia (RUDN University), 2008)
The article is devoted to the use of case-studies, group discussions, role-plays, imitative modeling and other interactive methods of teaching to build up students' interest in having communicative skills and socio-cultural knowledge necessary for effective cross-cultural communication.